1, 5-Anhydro-d-glucitol in vitreous humor and cerebrospinal fluid — A helpful tool for identification of diabetes and diabetic coma post mortem. (August 2018) - Sydow, Konrad; Kueting, Theresa; Musshoff, Frank; Madea, Burkhard; Hess, Cornelius
Highlights: Full validation of an APCI-LC–MS/MS method for quantitation of 1, 5-AG in VH and CSF. Low 1, 5-AG concentrations in CSF and VH indicate an ante mortem existing diabetes. 1, 5-AG concentrations <3.5 mg/ml in VH and CSF identify a possible diabetic coma Abstract: Since there are no characteristic morphological findings post mortem diagnosis of diabetes mellitus and identification of diabetic coma need to be confirmed by suitable biomarkers. The postmortem identification of preexisting hyperglycemia or diabetic coma can be difficult if the matrices for the determination of the established biomarkers are not available or the obtained results are close to the established cut-off values. 1, 5-Anhydroglucitol (1, 5-AG), the 1-deoxy form of glucose, competes with glucose for renal reabsorption. Therefore low serum concentrations of 1, 5-AG, reflect hyperglycemic excursions over the prior 1–2 weeks in diabetic patients. To evaluate postmortem 1, 5-AG concentrations in vitreous humor (VH) and cerebrospinal fluid (CSF), a liquid chromatographic mass spectrometric method for the quantification of 1, 5-AG in VH and CSF was developed and validated according to international guidelines. In order to establish a cut-off for the identification of an ante mortem existing diabetes and the diagnosis of a diabetic coma in deceased the relationships between 1, 5-AG concentrations in VH and CSF to other diabetes associated biochemical parameters of 47 non-diabetic, 86 diabetic and 9 cases of diabetic coma were examined. In 83 of these cases, both matrices could be obtained and analyzed. Comparisons of the respective HbA1c, Glucose in VH or Sum-formula of Traub to 1, 5-AG concentrations in VH and CSF resulted in correlation coefficients R 2 ≤ 0.2. For the application of 1, 5-AG concentrations in VH against CSF, a linear regression gave a correlation coefficient of R 2 = 0.955. Comparable linear correlations of 1, 5-AG concentrations could be observed between VH and femoral venous blood (FVB) (R 2 = 0.839) as well as between CSF and FVB (R 2 = 0.756). Due to overlapping concentration ranges, the determination of a reliable cut-off for the differentiation of diabetic disease to diabetic coma cases was not possible. However, the 1, 5-AG concentrations in VH and CSF in cases of deceased diabetics were significantly lower (p < 0.05) than in non-diabetic deceased and therefore indicate a pre-existing diabetes or even a diabetic coma as the cause of death.